The pest status and integrated management programme of carob moth, Ectomyelois ceratoniae Zeller, attacking citrus in South Africa - Thackeray, Sean Robin (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2017)
The carob moth, Ectomyelois ceratoniae Zeller, is a pest of agricultural commodities and stored products around the world. Carob moth is known to infest citrus in the Mediterranean region and in southern Africa. In grapefruit cultivars, carob moth infestations are associated with high levels of mealybug. However, although this relationship has been observed in other citrus types such as Navel oranges, this has never been quantified. A recent survey of infested fruit from various production areas in South Africa indicated that the pest status of carob moth on Navel oranges may have been underestimated. As a result of the incidental pest status of carob moth on citrus in South Africa in the past, a species specific integrated pest management (IPM) programme does not exist. Therefore, the overriding aim of this theses was to evaluate the pest status of carob moth in citrus and establish a species specific IPM programme by determine the autecology of carob moth in citrus. Reliable methods for monitoring carob moth in citrus orchards both for producers and for research purposes were developed. A user-friendly monitoring method for determining weekly carob moth infestation through dropped fruit was suitable for producers. A timed scouting method was also developed; although the accuracy of this method varied with the experience of the scout. The pest status of carob moth was highest in the Loskop Valley, Nelspruit and the Vaalharts production areas and economic injury to growers ranged from R512.35 to R3 719.80 per hectare as a direct result of infestation. No infestation was recorded in the Sundays River Valley and Citrusdal production areas over both the 2014-15 and 201516 growing seasons. A laboratory study showed the survival of carob moth larvae infesting citrus is less than 10% in the absence of mealybug. However, this increases to almost 40% in the presence of mealybug residues and sooty mould. There was a significant relationship between carob infestation at harvest and mealybug infestation in the middle months of the growing season. The relationship between carob moth and mealybug indicates that current production guidelines for the management of mealybug in citrus may need to be amended. Consequently, it is proposed that an orchard with a history of carob moth infestation and a high mealybug infestation in the previous season should be subjected to an early season preventative application of a registered control product. Also, if mealybug infestation in December is higher than a 5% of fruit per tree, then a corrective application of a registered product is recommended. The application of 2,4-D at petal drop reduced the size of the navel-end opening, decreasing the proportion of mealybug found in the navel-end, subsequently reducing carob moth infestation, resulting in a direct benefit for producers. Products registered for the control of false codling moth (FCM), Thaumatotibia leucotreta Meyrick, were effective in reducing carob moth infestation. In a spray trial conducted over two seasons, Delegate® and Runner® reduced infestation significantly in the 2014-15 season (over 80%), while only Delegate® was effective in the 2015-16 season (over 80%). If a late season corrective chemical application is targeted at both FCM and carob moth, this application should take place between 6-7 weeks prior to harvest. The mating disruption product, SPLAT® EC, reduced carob moth infestation by 70% compared to the untreated control. A laboratory culture was established and head-capsule size categories were determined for all five carob moth instars. A parasitoid survey indicated that parasitism of carob moth larvae is generally less than 5% in citrus orchards and a new species of Braconidae was described as Phanterotoma carobivora van Achterberg and Thackeray. Carob moth fifth instar were found to be the most cold-tolerant larval stage, and were shown to be more cold susceptible than the most cold-tolerant FCM instars at -0.55ºC for eighteen days. This cold treatment resulted in a mortality of 94.6% fifth instar carob moth compared to a combined fourth and fifth instar mortality of 87.8% for FCM after eighteen days. These results indicate that post-harvest cold treatments targeting FCM will be as, if not more, effective against carob moth, suggesting that current phytosanitary legislation for carob moth should be amended to incorporate this study's findings.
Keywords: Uncatalogued